Social media in Latin America: deepening or bridging gaps in protest participation?. Issue 5 (12th September 2016) - Valenzuela, Sebastián; Somma, Nicolás M.; Scherman, Andrés; Arriagada, Arturo
Abstract : Purpose: The purpose of this paper is to explore the relationship between social media use and protest participation in Latin America. It advances two questions. First, does social media increase the chances of protest participation at the individual level, as prior research shows for advanced democracies? Second, in a region with glaring economic and political inequalities, does social media deepen or reduce the gaps in protest participation that exist among men and women, the young and the old, different social classes, or people with varying levels of political engagement? Design/methodology/approach: The paper uses cross-sectional Latin American Public Opinion Project survey data from 2012 representing the adult population of 17 Latin American countries. It presents binary logistic regression models with protest participation as the dependent variable, social media use for political purposes as the main independent variable, control variables, and interactions. Findings: Using social media for political purposes significantly increases protest chances – it is the second strongest predictor. Additionally, social media reduces protest gaps associated with individuals' age, gender, psychological engagement with politics, and recruitment networks. Originality/value: First, the paper shows that the contribution of social media to collective protest travels beyond advanced democracies – it also holds for more unequal regions with weaker democratic trajectories like Latin America. Second, it shows that social media may mitigate participatory inequalities not only, as shown by past research, regarding institutional participation (e.g. voting), but also regarding contentious tactics.